Application of biomass extracted water-soluble binder for lithium-ion battery - Zhang, Qihang (2019)
Lithium-ion battery (LIB) is one of the most important energy storage devices used in various fields around the world, ranging from portable devices to electrical vehicles. However, most LIBs in the market use graphite as anode materials and their capacity (372 mAh/g) cannot meet the growing requirements of human development. Thus, silicon (with high theoretical capacity of 4000 mAh/g), has been widely investigated due to its great potential to be used as active materials for new generation batteries. Nevertheless, the huge volume expansion during cycling of Si is a big challenge urgently needs to be solved. In this regard, binders plays a crucial role in managing the problem. Anode of LIBs consists of three major parts, including active material, conductive material, and binder. Binder keeps anode integrated, ensuring continuous contact between the active material and conductive material. However, traditional binder polyvinylidene difluoride (PVDF) cannot meet the requirements for silicon-based anode. Thus, in this project, a new kind of organic binder is developed for silicon batteries. The binder here is one kind of pectin extracted from citrus peels, which is widely available and environmental friendly. Besides, unlike PVDF, the pectin binder is water-soluble, so it is easy and healthy to be used. Besides the alternation of binder, the modification of Si anode is also necessary. Considering the properties of nanosilicon and graphene, a composites consists of silicon and graphene is synthesized as anode material, and the batteries demonstrated promising performance. Firstly, 10 wt. %, 30 wt. % and 50 wt. % graphene is mixed into nanosilicon to obtain active material, afterwards fabricated into half-cell battery. The batteries achieved capacity retention rate of 34.8%, 25.3% and 52.6% after 100 cycles and under the current density of 1000 mA/g, respectively. The composites with 50 wt. % graphene outperforms other two composites. To further increase its capacity retention rate, the mass ratio of graphene is increased to 75 wt. %. Under this condition, the battery finally achieves less than 30% capacity loss after 200 cycles. The graphene doped into composites so far are obtained through thermal striping process, which causes the poor ability of graphene to disperse uniformly in water. The following inhomogeneous mixing decrease stability of electrode. Taking this factor into account, another lab-made graphene or RGO (reduced graphene oxide) is employed in anode to replace the commercial counterparty, and the final capacity retention rate reaches more than 70% after 100 cycles under 600 mA/g, which is two times better than the graphene originally used. The comparison between PVDF and pectin is also carried out. After 50 cycles, the capacity difference between PVDF and pectin expands to 500 mAh/g while they have almost the same initial capacity. Other tests, including scanning electron microscopy and mechanical tests are also carried out. In addition, the modification of binder is conducted. The pectin with citric acid undergoing an esterification reaction under 120 ℃ for 2 hours ending up with forming a strong network that can help hold the electrode structure, and keep it intact. The resulting electrode shows a better stability than the former electrode with pure pectin binder. After 100 cycles, the specific capacity exceeds its initial capacity, which demonstrates the self-healing property of the new binder. Besides, the binder is also applied to sodium ion battery with red phosphorus/graphene composites as anode materials. The 16-hour ball milled composites with pectin shows impressive stability. However, the specific capacity is relatively lower due to the introducing of other elements during the intensive ball milling process. Finally, the specific ways that this project solves the initial problem are explained as below and some feasible ways to further improve the performance of LIBs are proposed.